Reading Anxiety and Reading Comprehension in Senior High School Students - Yuni Kartika; Ridha Ilma; Renny Kurnia Sari (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2023)
There is an indication that language anxiety impairs one’s ability to perform a language. Anxiety was one of the factors that affected reading activities since it is up to humans to control their own anxiety in order to improve their reading comprehension. This study aimed to examine the correlation and the contribution of students' reading anxiety to their reading comprehension This study utilized quantitative research by employing a correlational research design. To collect data for this study, 88 students from one of the senior high schools in Banyuasin, South Sumatra, were chosen utilizing the cluster sampling technique. A reading anxiety questionnaire and a reading comprehension test were instruments to collect the data. The findings revealed that there was no significant correlation between students' reading anxiety and reading comprehension, with the correlation coefficient or R-value (.063) being lower than r-table (0.177). Furthermore, the significant level (sig.2-tailed) was (0.599). It showed that p (0.559) was more than (0.05). There was no contribution between students' reading anxiety and reading comprehension in this study since there was no significant association between reading anxiety and reading comprehension. The study's findings demonstrated that students' reading anxiety had no effect on their ability to comprehend what they read.